Do Mesenchymal Stem Cells Derived From Atypical Lipomatous Tumors Have Greater Differentiation Potency Than Cells From Normal Adipose Tissues?. Issue 6 (June 2017) - Inatani, Hiroyuki; Yamamoto, Norio; Hayashi, Katsuhiro; Kimura, Hiroaki; Takeuchi, Akihiko; Miwa, Shinji; Higuchi, Takashi; Abe, Kensaku; Taniguchi, Yuta; Yamada, Satoshi; Asai, Kiyofumi; Otsuka, Takanobu; et al.
Abstract: Background: The p53 protein in mesenchymal stem cells (MSCs) regulates differentiation to osteogenic or adipogenic lineage. Because p53 function is depressed in most malignancies, if MSCs in malignancy also have p53 hypofunction, differentiation therapy to osteogenic or adipogenic lineage may be an effective treatment. We therefore wished to begin to explore this idea by evaluating atypical lipomatous tumor/well‐differentiated liposarcoma (ALT/WDL) cells, because murine double minute 2 (MDM2) gene amplification, which leads to p53 hypofunction, is found in almost all ALT/WDLs. Questions/purposes: We compared osteogenic and adipogenic differentiation potency between MSCs isolated and cultured from normal adipose tissues and ALT/WDLs from the same patients. Methods: During tumor resections in six patients with ALT/WDL, we analyzed 3 mL of tumor, and for comparison, we harvested a similar amount of normal‐appearing subcutaneous adipose tissue from an area remote from the tumor for comparison. Adipogenic differentiation potency was quantitatively assessed using spectrometry after oil red O staining. Osteogenic differentiation potency was semiquantitatively assessed by measuring a specific colored area after alkaline phosphatase (ALP) and alizarin red S staining. ALP is related to preosseous cellular metabolism, and alizarin red is related to calcium deposits in cell culture. There were three observers for each assessment, and each assessment (including induced‐differentiation and histologic analysis) was performed in duplicate. We then analyzed the mechanism of the difference of osteogenic differentiation potency using the MDM2‐specific inhibitor Nutlin‐3 at various concentrations. Results: In terms of adipogenic differentiation potency, contrary to our expectations, more fatty acid droplets were observed in MSCs derived from normal fat than in MSCs derived from ALT/WDL, although we found no significant difference between MSCs derived from ALT/WDL and MSCs derived from normal fat; the mean differentiation potency values (normal adipose tissue versus ALT/WDL) (± SD) were 0.34 (SD, ± 0.13; 95% CI, 0.24‐0.44) versus 0.25 (SD, ± 0.10; 95% CI, 0.18‐0.33; p = 0.22). By contrast, we found greater osteogenic differentiation potency in MSCs derived from ALT/WDL than in MSCs derived from normal fat. The mean differentiation potency values (normal adipose tissue versus ALT/WDL) (±SD) based on ALP staining was 1.0 versus 17 (SD, ± 36; 95% CI, −2.8 to 38; p = 0.04). However, we found no differences based on alizarin red S staining; mean differentiation potency value (normal adipose tissue versus ALT/WDL) (± SD) was 1.0 versus 4.2 (SD, ± 4.8; 95% CI, 1.3‐7.2; p = 0.58). The gap of osteogenic differentiation potency between MSCs from normal adipose tissue and ALT/WDL was decreased as MDM2‐inhibitor Nutlin‐3 concentration increased. Conclusions: MSCs derived from ALT/WDL had higher osteogenic differentiation potency based on ALP staining, which disappeared as Nutlin‐3 concentration increased, suggesting that could be caused by amplified MDM2 in ALT/WDL. Future laboratory studies might mechanistically confirm the gene and protein expression, and based on the mechanism of the gap of differentiation potency, if p53 contrast between MSCs in tumor and normal tissue could be stimulated, less‐toxic and more‐effective differentiation therapy to MSCs in malignancies might be developed.